Design Space Exploration in the Mapping of Reversible Circuits to IBM Quantum Computers - Niemann, Philipp; Almeida, Alexandre A. A. de [UNESP]; Dueck, Gerhard; Drechsler, Rolf; Trost, A.; Zemva, A.; Skavhaug, A. (Ieee Computer Soc, 2020)
With more and more powerful quantum computers becoming available, there is an increasing interest in the efficient mapping of a given quantum circuit to a particular quantum computer (so-called technology mapping). In most cases, the limitations of the targeted quantum hardware have not been taken into account when generating these quantum circuits in the first place. Thus, the technology mapping is likely to induce a considerable overhead for such circuits. In this paper, we consider the realization of reversible circuits consisting of multiple-controlled Toffoli gates on IBM quantum computers. We show that choosing different quantum-level decompositions can indeed have a significant impact on the mapping overhead. Based on this observation, we present an approach to perform design space exploration to obtain quantum circuits with reduced overhead by exploiting information about the targeted quantum hardware as well as the reversible circuit. An experimental evaluation shows that this approach often leads to considerable reductions of the technology mapping overhead with negligible runtime.